Tegument Proteins of Kaposi’s Sarcoma-Associated Herpesvirus and Related Gamma-Herpesviruses - Sathish, Narayanan; Wang, Xin; Yuan, Yan (Frontiers in Microbiology, 2012)
A herpesvirus virion is composed of a viral genomic DNA-containing capsid surrounded by a viral envelope with glycoprotein spikes on its surface. Located between the capsid and the outer viral envelope is the virion tegument layer. Though the majority of the virion proteins are located in the tegument, this layer is less studied and was thought to be an amorphous structure. Over the last decade, a number of studies have indicated the presence of organized tegument structures across the spectrum of herpesviruses, implicating tegument components in critical steps governing the viral life cycle. In the case of Kaposi’s sarcoma-associated herpesvirus (KSHV), the etiological agent of Kaposi’s sarcoma (KS), several functions exerted by tegument proteins at different stages of the viral life cycle, inclusive of primary de novo infection and virion assembly, have been identified over the last several years. In this review, KSHV tegument components are catalogued and the occurrence of organized tegument structures in KSHV, built through interactions amongst the different virion proteins, is discussed in depth. The significant functional roles of the KSHV tegument proteins at different stages of the viral life cycle are elaborated under separate headings. Definitive functional roles exerted by tegument proteins of related gamma herpesviruses are also discussed. Since tegument proteins play key roles during viral assembly, viral entry, and represent an important interface for virus-host interactions, further research in this area should provide detailed insights into the functional capacity of the KSHV tegument, resulting in a better understanding of the viral life cycle.